Design Formulations for Predicting the Collision Damage of Steel Stiffened Cylinder and their Residual Strength under Combined Loads - Quang Thang Do; Van-Vu Huynh (New Approaches in Engineering Research Vol. 2, 2021)
This study aims to develop new formulations for predicting the permanent local denting damage of steel stiffened cylinders under dynamic lateral mass impact and their residual strength under combined loads. The considered scenarios could represent the collisions of offshore cylindrical structures with bow or stern of service vessels or floating objects. For this, two types of the stiffened cylinders, namely, stringer- and/or ring-stiffened cylinders, are generally main components of offshore marine structures used in semi-submersibles, submarines, tension legs of platforms (TLPs), and other various types of floating offshore structure are investigated. Before deriving the formulations, the numerical methods are developed using ABAQUS/Explicit to determine the deformation of these stiffened cylinder structures subjected to dynamic lateral mass impact. Next, rigorous parametric studies were performed on the actual design of full-scaled stiffened cylinder examples using the developed numerical method. Based on the rigorous numerical results, new simple design formulations to predict the maximum permanent local dent depth of a stiffened cylinder are derived through a regression study as the function of a non-dimensional energy parameter. Additionally, new simple design equations, which are used to predict the ultimate residual strength of the dented stiffened cylinders under combined loads are also proposed. The accuracy and reliability of the derived formulations are confirmed by comparing with the available test results, nonlinear FEA, and existing analytical and empirical equations in the literature. A good agreement with existing test data for ship-offshore structure collisions was achieved.